Internal Condition Analysis on Tourism Development of Bintan Regency 2019 - Rezki Feni Oktaviana; Adji Suradji Muhammad; Fitri Kurnianingsih; Mahadiansar Mahadiansar (Lasigo Akademia Indonesia, 2021)
The dynamics of tourism as an economic driver will greatly affect the environment in tourism development in Bintan Regency. One of the influencing environment is the internal condition in tourism management which is the reason for the need to map the problem. This paper focuses on environmental studies of the community, private sector, local government in the internal tourism of Bintan Regency in 2019. The research uses a literature study using secondary data which is analyzed in depth. The results showed that the internal analysis of tourism which includes 3 main components of tourism development, namely sustainable improvement of the tourism industry, improving institutional quality both in vertical agencies and the role of local communities which is very important in developing tourism in Bintan Regency. With the existence of three main components in the analysis of the internal environment for tourism in Bintan Regency, it is hoped that it can have a positive impact in a sustainable manner.